TOLERANCE TO PREVENT CULTURALLY DESTRUCTIVE BEHAVIORS OF YOUNG PEOPLE BASED SERVICE - Aytbayeva Gulchehra Yermekbayevna (Galaxy International Interdisciplinary Research Journal, 2024)
This article talks about the fact that tolerance is an attitude - a social value that ensures human rights, freedom and security , that education begins with creating an environment of tolerance, and about the definitions given to the concept of tolerance (tolerance) in the next decade.